2021
DOI: 10.1126/sciadv.abe4827
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota from patients with arteriosclerotic CSVD induces higher IL-17A production in neutrophils via activating RORγt

Abstract: The intestinal microbiota shape the host immune system and influence the outcomes of various neurological disorders. Arteriosclerotic cerebral small vessel disease (aCSVD) is highly prevalent among the elderly with its pathological mechanisms yet is incompletely understood. The current study investigated the ecology of gut microbiota in patients with aCSVD, particularly its impact on the host immune system. We reported that the altered composition of gut microbiota was associated with undesirable disease outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…The lower NLR reflects a greater diversity of gut microbiota [ 41 ]. Abnormal intestinal bacterial secretions can activate neutrophils, leukocytes, and lymphocytes to regulate the secretion of inflammatory factors [ 42 45 ]. However, our results indicate whether intestinal flora, inflammation, and immune function are in an upstream and downstream regulatory relationship or a parallel relationship during treatment with SLBZS.…”
Section: Discussionmentioning
confidence: 99%
“…The lower NLR reflects a greater diversity of gut microbiota [ 41 ]. Abnormal intestinal bacterial secretions can activate neutrophils, leukocytes, and lymphocytes to regulate the secretion of inflammatory factors [ 42 45 ]. However, our results indicate whether intestinal flora, inflammation, and immune function are in an upstream and downstream regulatory relationship or a parallel relationship during treatment with SLBZS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the role of microbiota in neurological disorders, but studies on WMH and SVD are relatively rare. Recently, Cai et al reported on the role of the gutimmune-brain axis in arteriosclerotic SVD pathophysiology (Cai et al, 2021). Another cross-sectional study indicated that some microbiota may increase the risk of WMH and SVD (Saji et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our data showed a positive correlation between PAGln and IS-T2D-associated gut microbiota, of which were positively correlated with NE. Dysregulation of gut microbiota in patients with arteriosclerotic cerebral small vessel disease has been reported to independently enhance the proin ammatory property of NE 73 . We thus inferred that IS-T2D-associated gut microbiota could exacerbate in ammation status of NE, and then combine with elevated PAGln in plasma to promote the formation of NETs, which may ultimately contribute to the aggravation of thromboin ammatory.…”
Section: Discussionmentioning
confidence: 99%